School Quality and the Development of Cognitive Skills between Age Four and Six - Lex Borghans; Bart H.H. Golsteyn; Ulf Zölitz (Institute for the Study of Labor (IZA), 2015)
This paper studies the extent to which young children develop their cognitive ability in high and low quality schools. We use a representative panel data set containing cognitive test scores of 4-6 year olds in Dutch schools. School quality is measured by the school's average achievement test score at age 12. Our results indicate that children in high-quality schools develop their skills substantially faster than those in low-quality schools. The results remain robust to the inclusion of initial ability, parental background, and neighborhood controls. Moreover, using proximity to higher-achieving schools as an instrument for school choice corroborates the results. The robustness of the results points toward a causal interpretation, although it is not possible to erase all doubt about unobserved confounding factors.
Keywords: I2; I24; J24; 330; cognitive skills; child development; school quality